A Comparative Study on the Use of First-Person Pronouns in Ten International Diplomatic Speeches - Pokhrel, Surendra (REiLA : Journal of Research and Innovation in Language, 2022)
This paper explores how world leaders use first-person pronouns in diplomatic speeches as a case study on how stance is communicated in high-stakes situations. The dataset comprises ten speeches to security and the economy given by heads of state/governments to their counterparts at international conferences/summits. The data were analysed from a quantitative/corpus-linguistic perspective using AntConc (Anthony, 2021) to summarise general patterns of personal pronoun use and then from a qualitative/discourse-analytical perspective, identifying specifically related examples for more detailed interpretation in context. The contextual features considered for the critical discourse analysis were gender, ideology, and the political systems of the speaker’s country. The results showed that most lead favoured the plural first-person pronoun “we” over the singular “I”. This was especially marked for the Middle Eastern leaders in the sample. The plural form was used for two main functions: (i) audience-inclusivity, referring to the audience of delegates/attendees, and (ii) audience-exclusivity, referring to the nation represented by the speaker. The distribution of these functions in the individual speeches varied greatly, ranging from extreme inclusive use (85%; Temer [Brazil]) to extreme exclusive use (65%; Putin [Russia]); this was largely predictable based on the speaker’s role at the event (e.g., facilitator vs dissenter from a consensus view) and the level of perceived national power. “I” was found to be used mostly at the beginning of the speeches to extend gratitude to the organisers. However, it was often deployed to increase the speaker’s self-dedication throughout an address. Similarly, whereas deployed throughout the speeches to establish a sense of communal rapport between the audience and the speaker. The evidence does not suggest any major differences in the usage of first-person pronouns based on gender, as shown by similarities in the speeches of German Chancellor Merkel and Bangladeshi Prime Minister Hasina.